2014
DOI: 10.1016/s2221-1691(14)60236-7
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin as a preventive resistance agent in MCF–7 breast cancer cells line resistance to doxorubicin

Abstract: Hesperidin has cytotoxic effect on MCF-7/Dox cells with IC50 of 11 µmol/L. Hesperidin did not increased the apoptotic induction combined with doxorubicin. Co-chemotherapy application of doxorubicin and hesperidin on MCF-7/Dox cells showed synergism effect through inhibition of Pgp expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 19 publications
0
42
0
3
Order By: Relevance
“…Drug chemosensitivity have been investigated in the several models of breast cancer cell such as T47D, WiDr colon cancer cells, MCF-7, MCF-7/Dox and showed various cytotoxic effects (Febriansah, et al, 2014;Hermawan, et al, 2010;Putri, et al, 2016). This study explored the effect of doxorubicin on triple negative breast cancer cell, 4T1, that is highly metastasis in breast and HER2-overexpresed cell, MCF-7/HER2.…”
Section: Discussionmentioning
confidence: 99%
“…Drug chemosensitivity have been investigated in the several models of breast cancer cell such as T47D, WiDr colon cancer cells, MCF-7, MCF-7/Dox and showed various cytotoxic effects (Febriansah, et al, 2014;Hermawan, et al, 2010;Putri, et al, 2016). This study explored the effect of doxorubicin on triple negative breast cancer cell, 4T1, that is highly metastasis in breast and HER2-overexpresed cell, MCF-7/HER2.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study reported that the presence of methoxy groups at the C-3' position of the B ring increase in anticancer antivities [6]. Chalcone compound with α,β-unsaturated carbonyl group is likely responsible for maximal inhibition cancer cell lines 4,9 . The previous study reported that chalcones with α,β-unsaturated carbonyl group greater cytotoxicity than without α,β-unsaturated carbonyl group in colon cancer (HT-29) and breast cancer (MCF-7) cell lines [4].…”
Section: Introductionmentioning
confidence: 97%
“…The previous study reported that chalcones with α,β-unsaturated carbonyl group greater cytotoxicity than without α,β-unsaturated carbonyl group in colon cancer (HT-29) and breast cancer (MCF-7) cell lines [4]. The 2-hydroxychalcone derivatives without α,β-unsaturated carbonyl group were inefficient for inhibition cancer cell lines [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1970s, Dox has been considered one of the most effective agents for the treatment of advanced breast cancer (10). However, recent studies have demonstrated that numerous cancer cell types, including breast cancer cells, are resistant to the apoptosis-inducing effects of Dox (11)(12)(13). Therefore, the identification of sensitizing agents that are able to increase the potency of Dox at low doses with clinically acceptable adverse effects may help to improve the treatment of breast cancer.…”
Section: Introductionmentioning
confidence: 99%